LIBRARY USE FROM DISCIPLINE CONTEXT: ANALYSIS OF PERSONAL TRAITS AND ATTITUDES OF UNDERGRADUATES - Karunanayake, Anura (Faculdade de Filosofia e Ciências, 2016)
ABSTRACT: This paper identifies the patterns of library use of undergraduates from discipline context based on their personal traits and attitude or Mode of library use. Medical and Arts undergraduates’ personal traits and attitudes are examined. Twelve variables which represent personal traits and six attitudes are observed. Descriptive analysis is used to measures the personal traits by mean values and Chi-square and ANOVA tests was used to identify the statistical differences of attitudes by disciplines. The results found that personal traits make them different in libraries. The students in the two discipline areas turned out to have very similar characteristics in traits and displayed most pronounce diversity in library use. There are significant differences in the attitude of library use by discipline. Need of library services by personal traits and attitudes in discipline context are highly required. Incorporating these findings with the existing libraries or ameliorating the services in general has a practical impact on utmost user satisfaction.